2013
DOI: 10.1177/1757913912466948
|View full text |Cite
|
Sign up to set email alerts
|

Eudaimonic well-being and community arts participation

Abstract: Arts and health researchers might usefully draw from theories of well-being from positive psychology. Both fields are compatible in that they share an interest in human flourishing and understanding of wellness as more than an absence of dysfunction or disease. Further research is needed to ascertain whether the limited results presented here are representative of other populations. What does seem evident is that arts projects have a broad appeal and can be highly inclusive, accommodating participants with div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
(22 reference statements)
4
32
0
1
Order By: Relevance
“…It was noted that living in a care home can be socially isolating and such trips were beneficial and enjoyable, in keeping with other studies (Cameron et al, 2013;Roberts, Camic, & Springham, 2011;Swindells et al, 2013). Benefits were not just limited to the visits but continued in terms of friendships between residents, care staff seeing older people in a new light because of social interaction and creative activity.…”
Section: Discussionmentioning
confidence: 55%
“…It was noted that living in a care home can be socially isolating and such trips were beneficial and enjoyable, in keeping with other studies (Cameron et al, 2013;Roberts, Camic, & Springham, 2011;Swindells et al, 2013). Benefits were not just limited to the visits but continued in terms of friendships between residents, care staff seeing older people in a new light because of social interaction and creative activity.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, the analysis above suggests that there is considerable applied potential in harnessing artistic modalities to promote wellbeing (and associated outcomes such as cognitive development Schnee, 1996); and older adults (e.g., visual art-based interventions in the community; Swindells et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…When they chose an activity that was related to their passion, participants reported that they connected with others from the group and learned something that interested them. The importance of the activity and its social context was also found in previous studies (Brownell et al, 2015;Lloyd & Little, 2010;Swindells et al, 2013). The explanation of why the selected activity is so essential derives from the participant's intrinsic motivation, another concept of SDT that has shown to effect need fulfillment (Deci & Ryan, 1980).…”
mentioning
confidence: 77%
“…Because the basic psychological needs are universal aspects of human functioning, this seems likely. Earlier studies indicated that SDT elements are described as important, even though the intervention, the interview scheme, nor the analysis was based on SDT (Brownell et al, 2015;Swindells et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation